2007
DOI: 10.1139/g07-038
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the trifunctional histidine biosynthesis gene (his) in cerealPhaeosphaeriaspecies

Abstract: Phaeosphaeria species are important causal agents of Stagonospora leaf blotch diseases in cereals. In this study, the nucleotide sequence and deduced polypeptide of the trifunctional histidine biosynthesis gene (his) are used to investigate the phylogenetic relationships and provide molecular identification among cereal Phaeosphaeria species. The full-length sequences of the his gene were obtained by PCR amplification and compared among cereal Phaeosphaeria species. The coding sequence of the his gene in wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Extraction of total RNA mainly followed the protocols described previously (Wang et al 2007). The mycelia were harvested and flash-frozen in liquid nitrogen.…”
Section: Gene Amplification and Sequencing Of Genomic Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction of total RNA mainly followed the protocols described previously (Wang et al 2007). The mycelia were harvested and flash-frozen in liquid nitrogen.…”
Section: Gene Amplification and Sequencing Of Genomic Dnamentioning
confidence: 99%
“…Total RNA was extracted from mortar/pestle pulverized mycelia using the RNeasy Plant Mini Kit according to the manufacturer's instructions (Qiagen Inc., Valencia, CA) and treated with RNase-Free DNase I enzyme (Roche Diagnostics Corporation, Indianapolis, IN). Lack of residual gDNA in total RNA was evidenced by not being able to amplify the histidinol dehydrogenase (Hdh1) gene fragment using the primer set 15A/12-1 (ATGCCGGCAGGACCCAGTGA/CTATCAAG CTACGCCAAGTCGC) (Wang et al 2007). The firststrand (1x) cDNA was synthesized with random primer p(dN) 6 and the First Strand cDNA Synthesis Kit (Roche Diagnostics Corporation, Indianapolis, IN).…”
Section: Gene Amplification and Sequencing Of Genomic Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…From these, two sets of primer pairs were selected for each of nine genes, and one primer set was selected for Hdh2. In addition, the gene sequences encoding MAP kinase (Mak2), trifunctional histidine biosynthesis (his) and β-tubulin (tubA) were analysed in two parental isolates Solomon et al 2006;Wang et al 2007). No nucleotide variation was identified in these three genes.…”
Section: Polymorphism Of the Genes And Est-derived Ssrs Markers Betwementioning
confidence: 99%
“…Restriction fragment length polymorphisms (RFLPs) (Ueng and Chen, 1994) and ITS sequences (Ueng et al, 1998) confirmed genetic differences between the two biotypes and led to the proposal to split Pat into three groups, Pat1, Pat2 and Pat3. Since 1998, the species complex was analyzed using six additional single gene phylogenies including mating-type loci (Bennett et al, 2003;Ueng et al, 2003), b-tubulin (tubA) (Malkus et al, 2005), b-glucosidase (bgl1) (Reszka et al, 2005), RNA polymerase II (Arkadiusz et al, 2006) and histidine synthase (his) (Wang et al, 2007). Until now, the phylogenetic relationships among these Phaeosphaeria spp.…”
Section: Introductionmentioning
confidence: 99%